Mathematical Model of the Growth of Rosa Freedom through Networks Neuronal - Jessica N. Castillo; Luigi O. Freire; John O. Ortega; Paul M. Tacle (Migration Letters, 2023)
In Ecuador, between 60 and 80 thousand rose plants are planted per hectare, to which a rigorous control is applied in the sowing and harvesting processes, considering environmental sustainability as an important factor in their production. The quality of the rose is determined by the size of the stem and buds that these have at the time of harvest, This model simulates the growth of the Freedom Rose in four different scenarios. The data was obtained from a field study, where the mi-cro and macro chemical nutrients were used in different combinations in each scenario, in the Neuronal Network of this study the first layer uses 12 qualitative parameters as inputs, the second layer is formed by 10 neurons and the third gives 4 outputs that are: width, stem height and width, button height.